Better Nate than ever [compact disc, unabridged] - Federle, Tim (Simon & Schuster Audio, 2014)
Nate Foster has big dreams. His whole life, he's wanted to star in a Broadway show. But how is Nate supposed to make his dreams come true when he's stuck in Jankburg, Pennsylvania, where no one, except his best pal Libby, appreciates a good show tune? With Libby's help, Nate plans a daring overnight escape to New York. There's an open casting call for E.T.: The Musical, and Nate knows this could be the difference between small-town blues and big-time stardom.